Optimization Strategy For Reducing Medical Record Documents At Regional Public Hospital - Nadhirah saffanah; Sri Wahyuni; Mariyanto Nurshamsul (International Journal of Multidisciplinary Learners, 2025)
Reduction of inactive medical record files has not been carried out by Buton Tengah Regional Hospital. Reduction of inactive medical record files is carried out five years after the last patient was treated in the hospital or five years after the patient died. This study aims to determine the optimization strategy for reducing medical record files. This study uses a qualitative descriptive research design. The subjects of the study were one submission officer and the head of the medical record department. The object of the study was the active medical record files belonging to Buton Tengah Regional Hospital. The results of this study were a decrease in human resources (HR) in the medical record unit by 16 people. The means to reduce the number of medical record files that were reduced were scanners and computers, but the infrastructure for storing inactive files. Meanwhile, the SOP for reducing medical record files and strategies for maximizing the reduction of inactive BRM are not yet available. In addition, Buton Tengah District Hospital has prepared a work plan for reducing medical record files which will be implemented in 2024, but the reduction of inactive files at Buton Tengah Hospital has not been implemented. So it is necessary to create a reduction SOP at Buton Tengah Hospital because currently there is only an SOP for retention and destruction. At Buton Tengah Hospital, there is no special place for inactive files. Therefore, it is necessary to create a special room for inactive files at Buton Tengah Regional Hospital.